C++/CLI Primer For .NET Development - Ragunathan, Vivek (Apress : Imprint: Apress, 2016)
Enter a world of hardcore back-end, server-side enterprise programming on the .NET platform. This book presents some of the important aspects of the C++/CLI language that often become a barrier preventing programmers from exploring further. The C++/CLI Primer is a powerful but compact book that will guide you through that barrier. Many of today's complex transactions and enterprise applications count on C++/CLI. Visual Studio 2015 and earlier versions support C++/CLI if you program using an IDE. C++/CLI is unattractive, clumsy, and hard when compared to other modern languages that run on the .NET platform. That's because it is powerful. Like light that can be viewed as a wave or particle, C++/CLI can be exercised as an unmanaged or managed or actually as the sandwich language to do mixed mode programming, which is its real power. That's also why it is unique. What You'll Learn Discover C++/CLI and why is it used in .NET programming Work with types, primitive types, object creation, and managed and abstract classes Use abstract classes in C++/CLI Harness the power of nullptre Implement code that uses boxing/unboxing Use equality/identity, properties, enums, strings, arrays, and more Who This Book Is For Experienced Microsoft .NET application developers, familiar with .NET framework and C++. .